Classification of Boolean Functions Where Affine Functions Are Uniformly Distributed. (31st October 2013) - Rout, Ranjeet Kumar; Pal Choudhury, Pabitra; Sahoo, Sudhakar
Abstract : The present paper on classification of n -variable Boolean functions highlights the process of classification in a coherent way such that each class contains a single affine Boolean function. Two unique and different methods have been devised for this classification. The first one is a recursive procedure that uses the Cartesian product of sets starting from the set of one variable Boolean functions. In the second method, the classification is done by changing some predefined bit positions with respect to the affine function belonging to that class. The bit positions which are changing also provide us information concerning the size and symmetry properties of the classes/subclasses in such a way that the members of classes/subclasses satisfy certain similar properties.